The effect of three desensitizing agents on dentin hypersensitivity: A randomized, split-mouth clinical trial - Torres, Carlos Rocha Gomes [UNESP]; Da Silva, Tânia Mara [UNESP]; Da Fonseca, Beatriz Maria [UNESP]; Sales, Ana Luísa Leme Simões [UNESP]; Holleben, Priscila [UNESP]; Di Nicolo, Rebeca [UNESP]; Borges, Alessandra Bühler [UNESP] (Operative Dentistry, 2014)
The aim of this study was to evaluate the efficacy of three desensitizing agents to provide relief to dentin hypersensitivity after one session in a four-week follow-up. Forty selected patients participated in a double-blind study following a split-mouth model. One application of the desensitizing agents (A, Admira Protect [Voco]; B, Bifluorid 12 [Voco]; and C, Colgate Pro-Relief in office [Colgate Palmolive]) was performed in three different quadrants for each patient. Each tooth was evaluated by tactile and evaporative stimuli, and the sensitivity response was measured using the Visual Analogue Scale. Evaluations were performed at baseline, immediately after treatment, and after one, two, three, and four weeks. The application of Kruskal-Wallis and Dunn multiple comparisons tests (5%) for both tactile and evaporative stimuli showed that all agents presented a significant desensitizing effect. In groups A and B this relief was maintained for four and three weeks, respectively, as measured by tactile stimulus and for four weeks with evaporative stimulus. The desensitizing effect for group C was maintained for two weeks for both tactile and evaporative stimuli. It is concluded that all desensitizing agents tested were effective in reducing sensitivity compared to baseline values. One application of Admira Protect and Bifluorid 12 presented a longer-lasting desensitizing effect than did Colgate Pro-Relief (applied in the office) on both tactile and evaporative stimuli.